An Analysis Of The Structure Of The Performance Of Traditional Arts Jheren Kencak Probolinggo - Indra Tjahyadi; Koko Hari Pramono; Abdurrahman Abdurrahman (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2023)
This research focuses on the performance structure contained in the Jheren Kencak traditional art that developed in Probolinggo Regency. The purpose of this study was to describe the structure of the traditional Jheren Kencak performing arts that developed in Probolinggo Regency. The method used in this research is descriptive qualitative method. Data collection techniques were carried out using interview techniques, observation, and literature study. Based on the analysis conducted, it was found that the Jheren Kencak traditional art that developed in Probolinggo Regency has a performance structure consisting of the following elements: (1) giro ketipungan, (2) jheren kember, (3) jheren tonggel, (4) tapel-napel (5) lawakan, (6) rak-arakan, and (7) mang-temang